Data and Safety Monitoring Board evaluation and management of a renal adverse event signal in TOPCAT. (21st November 2016) - Bristow, Michael R.; Sharma, Kavita; Assmann, Susan F.; Linas, Stuart; Gersh, Bernard J.; Grady, Christine; Rice, Madeline Murguia; Singh, Steven; Boineau, Robin; McKinlay, Sonja M.; Greenberg, Barry H.
Abstract: Clinical trial Data and Safety Monitoring Boards (DSMBs) have a primary obligation of ensuring study participant safety, while maintaining trial integrity. The role of DSMBs is expanding, and ideally should include post‐hoc reporting of deliberative processes related to clinically important safety issues or factors that could impact on future trial designs. We describe how the TOPCAT DSMB detected, investigated, and adjudicated an unexpectedly large renal adverse event signal midway through the trial, and offer general guidelines for dealing with similar unanticipated occurrences in future trials. The detection of a greater than expected incidence of deterioration in renal function, occurring in 6.1% of patients in the spironolactone arm compared with 3.9% in the placebo arm ( P = 0.009), led to an in‐depth DSMB review of associated study medication withdrawals and adverse events. The trial continued uninterrupted throughout the review, which reached the conclusions that spironolactone‐associated renal dysfunction did not compromise overall patient safety or interfere with a perceived efficacy signal. Although no discrete mechanism for the spironolactone‐associated renal adverse event signal was identified, likely possibilities are discussed. In clinical trials, DSMBs and co‐ordinating centres should have the resources to detect, investigate, and adjudicate unexpected safety issues, with goals of ensuring patient safety and preserving the potential for detection of therapeutic effectiveness. In TOPCAT, spironolactone‐associated renal dysfunction emerged as a potentially trial‐threatening adverse event and, although clinically important, did not lead to compromise of patient safety, trial interruption, termination, or apparent loss of treatment effectiveness.